THE HISTORY OF THE DEVELOPMENT OF THE UZBEK NATIONAL LANGUAGE IN THE 20TH CENTURY - M. O. Rahimova; F. O. Muhammadqodirova (Journal Park Publishing, 2022)
This article discusses the role of great representatives of the national renaissance in the development of the Uzbek language. The contribution to the development and formation of our national language by our enlightened pioneers such as Mahmudhoja Behbudi, Abdulhamid Cholpon and Abdurauf Fitrat is presented.
Keywords: Jadid, Third renaissance, Uzbek language, nation, national language.